Calibrating the cube transit model of UP Diliman - Tesoro, Carina R.; Tesoro, Celina R.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
An earlier study in 2017 by Eden and Saquing went into further development of the Cube Transit Model of UP Diliman based on the model used by the National Center for Transportation Studies for the pre-feasibility studies for the AGT. This study aimed to calibrate the model developed by the 2017 study to prepare it for use in modelling alternative scenarios, or for integration or expansion of the model to encompass a larger study area. This study explored three main calibration parameters, namely the input origin-destination matrices which make up the trip matrix of the model, the value of time parameter which quantifies a traveler's willingness to exchange money for time, and the link speed parameter which approximates travel conditions of units in transit. Secondary data was used to update the calibration parameters. The OD matrices were updated using the Furness Method, taking population ratios between the base and forecast years as growth factors, and values for the other parameters were sourced from JICA reports on infrastructure development in Metro Manila. The calibrated model was validated against observed data, with ridership in passengers, passenger-kilometers, and passenger-hours as validation parameters. Validation of the calibrated model resulted in a maximum of 76% deviation among all validation parameters.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- University of the Philippines; Transportation -- Mathematical models